Short-term exposure to fine particulate matter and asthma exacerbation: a large population-based case-crossover study in Southern Thailand - Suebsai Varopichetsan; Natthaya Bunplod; Racha Dejchanchaiwong; Perapong Tekasakul; Thammasin Ingviya (Environmental Health)
Abstract Background Asthma exacerbations remain a significant global health issue despite advances in management. Fine particulate matter (PM2.5, particles ≤ 2.5 μm in diameter) is a known trigger for asthma exacerbations. However, studies on the acute effects of PM2.5, particularly in regions with relatively low pollution levels, are limited. This study examined the time-lagged association between daily PM2.5 exposure and asthma exacerbations in Songkhla province, southern Thailand, where PM2.5 concentrations frequently approach the World Health Organization’s (WHO) Global Air Quality Guidelines. Approximately 41% of days during the study period had PM2.5 concentrations below the 2021 Guideline level of 15 µg/m³. Additionally, the province is periodically affected by seasonal transboundary haze from forest fires. Methods A case-crossover study was conducted using daily PM2.5 and meteorological data from January 2010 to December 2023, alongside health records of asthma patients from Songklanagarind Hospital. District-level daily PM2.5 concentrations were estimated through inverse distance weighted interpolation. Conditional logistic regression, incorporating time-lagged models and cubic splines, was applied. Results The study included 11,848 case days and 39,810 control days, with a mean daily PM2.5 concentration of 18.2 µg/m³. PM2.5 concentrations > 50 µg/m³ were significantly associated with asthma exacerbations at multiple time lags (lag0, lag2, and lag01 to lag03), with odds ratios ranging from 1.41 to 1.64, compared to the lowest concentration group (PM2.5 0–15 µg/m³). Temperature showed no significant effect, while relative humidity was positively associated with asthma exacerbations at lag3, lag06, and lag07. Subgroup analyses revealed associations between PM2.5 exposure and asthma exacerbations at early lags for both males and females. Additionally, children aged 6–11 years and 12–17 years exhibited greater susceptibility to asthma exacerbations, particularly at PM2.5 concentrations of 15–25 µg/m³. Conclusion This study underscores the short-term effects of PM2.5 on asthma exacerbations, particularly during high-pollution episodes of transboundary haze in regions that generally experience low levels of air pollution. These findings emphasize the importance of achieving the WHO air quality targets to mitigate the health impacts from PM2.5.